2001
DOI: 10.1093/jac/48.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of Campylobacter strains isolated from food animals in Belgium

Abstract: Campylobacter spp. are a frequent cause of diarrhoea in man, originating mostly from poultry. It has been suggested that the veterinary use of antibiotics is largely responsible for resistance in human isolates, particularly to quinolones. During a 6 month period from June to December 1998, 677 Campylobacter isolates were obtained from healthy poultry and pigs. Samples were taken at Belgian slaughterhouses. Species identification was performed by biochemical tests, multiplex PCR and SDS-PAGE of whole-cell prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
85
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 24 publications
19
85
2
3
Order By: Relevance
“…Several studies examined thermophilic Campylobacter in poultry and the findings indicated prevalence ranges of the Campylobacter from 3-98% with C. jejuni as the main isolates (Kapperud et al, 2003;Cardinale et al, 2003). Van Looveren et al (2001) found that among 677 Campylobacter isolates from broiler carcasses from Belgian slaughter houses, 79% was identified as C. jejuni.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examined thermophilic Campylobacter in poultry and the findings indicated prevalence ranges of the Campylobacter from 3-98% with C. jejuni as the main isolates (Kapperud et al, 2003;Cardinale et al, 2003). Van Looveren et al (2001) found that among 677 Campylobacter isolates from broiler carcasses from Belgian slaughter houses, 79% was identified as C. jejuni.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases of clinical Campylobacter enteritis are sufficiently mild or self-limiting not to require antimicrobial chemotherapy [6]. Nevertheless, in severe or recurrent cases where antibiotics are required, susceptibility testing is important to ensure appropriate and timely treatment [13,134,179]. Serious systemic infection may also be treated with an aminoglycoside such as gentamicin [153].…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…For the Enterobacteriaceae, biochemical identification was performed (API 20E system, Analytab Products, New York, NY). Hippurate hydrolysis was used to differentiate the Campylobacter isolates into Campylobacter jejuni (hippurate positive) and non-jejuni (hippurate negative) (Van Looveren et al, 2001). For the identification of enterotoxigenic E. coli (ETEC), five individual E. coli-like colonies were assayed for the production of heat-labile toxin (LT) and heat-stable toxin (ST), using direct and indirect GM 1 ELISA (Svennerholm and Wiklund, 1983;Sanchez et al, 1990).…”
Section: Bacteriologymentioning
confidence: 99%